Clinical Efficacy of Single Application Local Drug Delivery and Adjunctive Agents in Nonsurgical Periodontal Therapy: A Systematic Review and Network Meta-Analysis - Oi Leng Tan; Syarida Hasnur Safii; Masfueh Razali (MDPI AG, 2020)
This review aimed to rank the clinical efficacy of commercially available single-application local drug delivery and adjunctive agents (LDAs) compared with subgingival mechanical debridement (SMD) in nonsurgical periodontal therapy (NSPT). Randomized controlled clinical trials that compared LDAs against SMD alone or with placebo in adults (aged at least 18 years) diagnosed with periodontitis with a minimum of 6 months follow-up were included. A frequentist approach to random-effects network meta-analysis was implemented. The efficacies of the LDAs measured by probing pocket depth (PPD) reduction and clinical attachment level (CAL) gain were reported as mean difference (MD) with 95% confidence intervals (CIs). The treatments were ranked according to their P-score. Four network meta-analyses suggested that sulfonic/sulfuric acid gel (PPD MD −1.13 mm, 95% CI −1.74 to −0.53, P-score 0.91; CAL MD −1.09 mm, 95% CI −1.58 to −0.61, P-score 0.95) and doxycycline hyclate gel (PPD MD −0.90 mm, 95% CI −1.50 to −0.30, P-score 0.93; CAL MD −0.84 mm, 95% CI −1.40 to −0.28, P-score 0.92) were the most effective in reducing PPD and gaining CAL in split-mouth and parallel studies, respectively (moderate certainty of evidence). LDAs have differing efficacies, but they present with possible clinical significance over SMD alone in NSPT.